2002
DOI: 10.4049/jimmunol.168.5.2365
|View full text |Cite
|
Sign up to set email alerts
|

Txk, a Member of Nonreceptor Tyrosine Kinase of Tec Family, Acts as a Th1 Cell-Specific Transcription Factor and Regulates IFN-γ Gene Transcription

Abstract: Precise mechanisms responsible for Th1 cell activation and differentiation are not fully elucidated. We have recently reported that Txk, a member of Tec family nonreceptor tyrosine kinase, is expressed on Th1/Th0 cells, and Txk regulates specifically IFN-γ gene expression. In this study, we found that Txk bound to IFN-γ promoter region. Txk transfection increased transcriptional activity of IFN-γ promoter plus luciferase constructs severalfold, including IFN-γ promoter −538, −208, and −53. IFN-γ promoter −39 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 39 publications
(40 reference statements)
1
42
0
Order By: Relevance
“…Txk has been previously described as a Th1 cell-specific transcription factor, which regulates IFN-␥ gene transcription (45). Our Affymetrix data showed that its expression level was higher in Stat6-deficient cells compared with wt cells.…”
Section: And "#" (Differences Induced By Il-4 Comparing Wt and Stat6mentioning
confidence: 59%
“…Txk has been previously described as a Th1 cell-specific transcription factor, which regulates IFN-␥ gene transcription (45). Our Affymetrix data showed that its expression level was higher in Stat6-deficient cells compared with wt cells.…”
Section: And "#" (Differences Induced By Il-4 Comparing Wt and Stat6mentioning
confidence: 59%
“…A determining factor of CTL memory differentiation is the expression of IL-7R during the acute phase of infection (39). Genes like the Txk kinase and c-myb that are most commonly associated with thymocyte differentiation (40-42) may perhaps also act to facilitate T cell survival in the responding lymph nodes and spleen (42)(43)(44). Additional evidence for active transcriptional pathways in the splenic CD8 ϩ D b NP 366 ϩ set that could contribute to T cell survival comes from the identification of genes like pim1, which interacts with c-myb (45) and can enhance c-myb transcriptional activity (46).…”
Section: Discussionmentioning
confidence: 99%
“…(31). The other Th1 transcription factor predominantly expressed at this time point is Txk, which has been shown to directly bind to the IFN-␥ promoter and activate its transcription (32). Txk is highly expressed in resting naïve CD4 ϩ T cells and down-regulated after TCR engagement.…”
Section: Clustering Analysis Revealed That Th1͞2 Differentiation Expementioning
confidence: 99%